Quantitative biopharmaceutics classification system: The central role of dose/solubility ratio - Rinaki, E; Valsami, G.; Macheras, P. (PHARMACEUTICAL RESEARCH, 2003)
Purpose. To develop a quantitative biopharmaceutics drug classification system (QBCS) based on fundamental parameters controlling rate and extent of absorption. Methods. A simple absorption model that considers transit flow, dissolution, and permeation processes stochastically was used to illustrate the primary importance of dose/solubility ratio and permeability on drug absorption. Simple mean time considerations for dissolution, uptake, and transit were used to identify relationships between the extent of absorption and a drug's dissolution and permeability characteristics. Results. The QBCS developed relies on a ( permeability, dose/ solubility ratio) plane with cutoff points 2 x 10(-6) - 10(-5) cm/s for the permeability and 0.5 - 1 (unitless) for the dose/ solubility ratio axes. Permeability estimates, P-app are derived from Caco-2 studies, and a constant intestinal volume content of 250 ml is used to express the dose/ solubility ratio as a dimensionless quantity, q. A physiologic range of 250 - 500 ml was used to account for variability in the intestinal volume. Drugs are classified into the four quadrants of the plane around the cutoff points according to their Papp, q values, establishing four drug categories, i.e., I (P-app > 10(-5) cm/s, q less than or equal to 0.5), II (P-app > 10(-5) cm/s, q > 1), III (P-app < 2 x 10(-6) cm/s, q <= 0.5), and IV (P-app < 2 x 10(-6) cm/s, q > 1). A region for borderline drugs (2 x 10(-6) < P-app < 10(-5) cm/s, 0.5 < q < 1) was defined too. For category I, complete absorption is anticipated, whereas categories II and III exhibit dose/ solubility ratio - limited and permeability-limited absorption, respectively. For category IV, both permeability and dose/ solubility ratio are controlling drug absorption. Semiquantitative predictions of the extent of absorption were pointed out on the basis of mean time considerations for dissolution, uptake, and transit in conjunction with drug's dose/ solubility ratio and permeability characteristics. A set of 42 drugs were classified into the four categories, and the predictions of intestinal drug absorption were in accord with the experimental observations. Conclusions. The QBCS provides a basis for compound classification into four explicitly defined drug categories using the fundamental biopharmaceutical properties, permeability, and dose/ solubility ratio. Semiquantitative predictions for the extent of absorption are essentially based on these drug properties, which either determine or are strongly related to the in vivo kinetics of drug dissolution and intestinal wall permeation.
Keywords: biopharmaceutics classification system; Dissolution; dose/solubility ratio; Permeability; Solubility